PENGEMBANGAN POTENSI USAHA HASIL TERNAK BERBASIS POPULASI DAN KELEMBAGAAN DI PROVINSI JAWA BARAT - Iman Trisman; M. Munandar Sulaeman; Marina Sulistyati (Universitas Galuh, 2022)
The research was aimed to investigate business of development of livestock product based on animal population and institutional business. The research was conducted using Mix method namely quantitave and qualitative method. Quantitative method was used to determine the basic commodity based on population and institutional variables, then qualitative method was used to analyze the potential development of livestock products. The result showed there were seven regencies that have potential to develop beef cattle commodity businesses, namely Indramayu Regency, Kuningan Regency, Pangandaran Regency, Subang Regency, Tasikmalaya Regency, Sumedang Regency, and Majalengka Regency. Meanwhile, dairy cattle have the potential to be developed in six regencies, namely West Bandung regency, Cimahi Regency, Bandung Regency, Bogor Regency, Kuningan Regency, and Subang Regency. Toward, It is hoped that the business development of beef cattle and dairy cattle can be developed in these areas by empowering livestock groups and utilizing local resources.